Influence of Block Copolymer Concentration and Resin Crosslink Density on the Properties of UV‐Curable Methacrylate Resin Systems. Issue 10 (29th July 2022) - Demleitner, Martin; Schönl, Florian; Angermann, Jörg; Fässler, Pascal; Lamparth, Iris; Rist, Kai; Schnur, Thomas; Catel, Yohann; Rosenfeldt, Sabine; Retsch, Markus; Ruckdäschel, Holger; Altstädt, Volker
Abstract: Additive manufacturing is on the verge of replacing established processes in dentistry, as it offers the possibility of manufacturing individual parts simply and cost‐effectively. Due to its suitability for a wide variety of materials and, above all, its high precision, the focus is currently on stereolithographic processes. Intrinsic brittleness of the used multifunctional acrylic monomers remains however one of the major challenges. One promising concept is the use of block copolymers (BCPs) guaranteeing minor effects on 3D‐printing processing and UV‐curing due to initially at least partial solubility, and hence low viscosity impact. A polycaprolactone‐polysiloxane (PCL‐PDMS‐PCL) triblock copolymer is synthesized via ring‐opening polymerization of caprolactone and used in radical UV‐cured methacrylic resin systems. Small angle X‐ray scattering measurements reveal the self‐assembly of the BCPs to objects of around 20 nm prior to curing. Subsequently, thermo‐mechanical characterization is carried out by dynamic mechanical analysis, flexural testing, and fracture toughness measurements ( K IC ). Transmission electron microscopy and scanning electron microscopy micrographs show a homogenous distribution of the BCPs and effective toughening via cavitation and shear yielding. The influence of the crosslink density on the toughness and the high effectiveness of block copolymers for improving fracture toughness is clearly shown. Abstract : A synthesized tri block copolymer (BCP) shows excellent toughenability in a UV‐curable dimethacrylate resin system. With varying crosslink density of the resin, a BCP content of 5 wt% shows generally only a slight decrease in strength and modulus with sufficient improvement in fracture toughness. The nanoscale self‐assembly of the block copolymer before UV‐cure is demonstrated via small angle X‐ray scattering.